Quality of life, pain, depression, fatigue and sleep in patients with remission or mild fibromyalgia: a comparison with remission or low disease activity rheumatoid arthritis and healthy controls - Yidan Wang; Pengxiao Liu; Zihao Li; Shiya Wu; Meijuan Long; Yang Li; Juan Jiao; Zheng Xie (BMC Musculoskeletal Disorders)
Abstract Background Fibromyalgia is a chronic condition marked by widespread pain and various accompanying symptoms. Compared to healthy individuals and other rheumatic disease patients, it leads to more severe symptoms and a lower quality of life. Whether fibromyalgia patients in a mild activity or remission stage still experience core symptoms remains unclear. Objective To compare the severity of clinical symptoms and quality of life (QOL) in patients with remission or mild fibromyalgia (RFM) and remission or low disease activity in rheumatoid arthritis (RRA) patients and healthy controls (HCs) to investigate whether fibromyalgia in a stable stage can be disease-free. Methods This cross-sectional study evaluated a total of 266 RFM and 252 RRA patients and 50 HCs using Revised Fibromyalgia Impact Questionnaire (FIQR), Widespread Pain Index (WPI), Pain Visual Analogue Scale (VAS), Numerical Rating Scale, Multidimensional Fatigue Inventory (MFI-20), Pittsburgh Sleep Quality Index (PSQI), and Beck Depression Inventory (BDI), and Short Form-36 Health Status Questionnaire (SF-36). Results The FIQR total score and pain VAS, MFI, and PSQI scores were higher in RFM and RRA patients compared to HCs (P < 0.001). RFM patients had higher BDI and WPI scores than RRA patients (P < 0.001). The majority of RFM patients (97.4%) had more than two pain sites, with moderate-to-severe pain (78.2%), sleep disorders (85.0%), and depression (53.4%), all of which were significantly higher than those in RRA patients (P < 0.001). RFM patients also had lower scores in SF-36 physical and mental component summaries and subscores for role physical, pain index, general health perception, vitality, and mental health index, but a higher social functioning score than RRA patients (P < 0.001). Conclusion Despite being in a mild activity or remission stage, RFM patients experience more severe symptoms and poorer QOL than RRA patients. Therefore, individualized evaluation and intensive management are required. Trial registration ClinicalTrials.gov Identifier: NCT02449395, registered on May 20, 2015.